Wax Myrtle, Morella cerifera Synonym: Myrica cerifera - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS, 2018)
Wax myrtle is one the most widespread plants in Florida, and it is found in coastal states west to Texas and north to New Jersey. The wax found around seeds can be melted down to make candles. The fruits of wax myrtle are important for birds and other wildlife, and the plant is a larval host for the banded hairstreak and redbanded hairstreak butterflies (Satyrium calanus and Calycopis cecrops, respectively) (Lotts and Naberhaus 2017). Wax myrtle has been shown to contribute substantial nitrogen addition to soils via symbiotic relationships with nitrogen-fixing microorganisms residing in soils (Permar and Fisher 1983). https://edis.ifas.ufl.edu/sg176